The dual environmental and economic effects of the emission trading scheme under local fiscal pressure: “efficient markets” and “promising governments” - Song, Yuyuan; Cheng, Qinliang; Gan, Xuewei; Huang, Hengjun (Frontiers in Environmental Science, 2023)
Compared with developed economies, China implements the Emission Trading Scheme (ETS) within a fundamentally distinct political-economic-institutional context. This study aims to investigate the internal mechanisms and external constraints of ETS in achieving dual benefits of environmental preservation and economic advancement within the institutional context of fiscal decentralization. We demonstrate that the transmission from emission reduction to economic returns inherently facilitates the realization of dual benefits, and further propose a restrictive effect of local fiscal pressure on ETS effectiveness. Using panel data of 284 prefectural-level cities from 2003 to 2017, we conduct a quasi-experiment based on China's ETS pilot policy in 2007. The results indicate three primary conclusions: First, the implementation of ETS in China generally yields dual environmental-economic benefits, with emission reduction serving as a transmission channel for realizing economic gains. Second, high fiscal pressure on local governments not only directly undermines policy effects but also indirectly affects the transmission channel. Finally, the dual benefits have been realized in eastern China, but not yet in the central and western regions. This study contributes to the research on market-oriented environmental governance under fiscal decentralization. The theoretical logic of this study can be applied to a wide range of market-based mechanisms for green factors trading, providing valuable insights for countries facing similar challenges.